Denture Hygiene Knowledge, Attitudes, and Practices Toward Patient Education in Denture Care among Dental Clinicians in Benghazi City, Libya - Elhddad, Abdelsalam I.; Elnaili, Salma A.; Beaayou, Hawwa S; Bushwigeer, Sara S. (Libyan Journal of Dentistry, 2023)
Background: Denture cleaning is essential to prevent malodor, poor aesthetics and the accumulation of plaque/calculus with its deleterious effects on the mucosa. Moreover, denture and mucosal tissues of the edentulous mouth's hygiene, especially in the elderly are essential for overall health. Therefore, the present study was conducted to assess the denture hygiene knowledge and attitudes toward patient education in denture care among dentists in Benghazi, Libya. Materials & Methods: The present questionnaire survey was conducted on 180 dentists. A self-administrated questionnaire was designed to gather the socio-demographic characteristics, assess the denture hygiene knowledge, attitudes and practices among dental clinicians. The data was entered and analyzed using the Statistical Package for Social Science (SPSS Version 20 for Windows, SPSS Inc. Chicago, IL). Results: A total of 155 questionnaires had been returned to the researcher giving a response rate 86 %. The sample comprised of 74.8% of females and 25.2% of males. About 57.4% of participants were general dental practitioner. While 17.4% and 25.2% of them specialist (prosthodontics and non -prosthodontics). About 87.6% of dental general practitioner had aware about accumulation of oral biofilm on denture, but almost of them did not know that the oral biofilm associated with denture stomatitis. While high rates of specialists (prosthodontics 74.1% and non-prosthodontics 64.1%) had positive attitude in compared with general practitioner 48.3% (The difference was significant) about explaining denture hygiene instructions to old patients. All of prosthodontics gave patient's instruction regarding the denture cleansing methods at the time of denture delivery 64% of them used verbal medium for instruction delivery. Conclusion: Dental general practitioner had limited knowledge and attitudes toward patient education in denture care whereas specialists had sufficient denture hygiene knowledge, attitudes and practices toward patient education in denture care.